Prediction of Vaginal Delivery Using Fetal Head Descent Assessed Using Transperineal Ultrasound: Penilaian Penurunan Kepala dengan USG Transperineal untuk Penentuan Keberhasilan Persalinan Pervaginam - Yudianto B Saroyo; Mahendri D Danarti (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To evaluate the use of transperineal ultrasound in predicting the successfulness of vaginal delivery. Methods: This was a prospective study conducted at Karawang District Hospital during the period between March 2016 and May 2016. Inclusion criteria were term pregnancy, singleton live head presentation, and active phase of labor. Using transperineal ultrasound, fetal head perineum distance, and angle of progression within relaxation phase between contraction were being calculated. Results: There were 306 subjects who delivered vaginally. The cut off value for fetal head perineum distance as a predictor of vaginal delivery was 43.5 mm (sensitivity 91%, specificity 78%), with area under a curve of 82% (95% CI 69 - 95%, p < 0.01); while angle of progression is 107Â° (sensitivity 80 %, specificity 97%), with Area under curve is 96.4% (95% CI 87 - 99%, p < 0.01). Conclusion: Fetal head perineum distance and angle of progression can predict the successfulness of vaginal delivery. [Indones J Obstet Gynecol 2017; 5-3: 149-153] Keywords: angle of progression, fetal head-perineum distance, prediction of vaginal delivery, transperineal ultrasound